2003
DOI: 10.1046/j.1365-8711.2003.06348.x
|View full text |Cite
|
Sign up to set email alerts
|

Radar meteoroid orbit stream searches using cluster analysis

Abstract: The single‐linkage cluster analysis technique is here applied to the data set provided by the AMOR meteoroid orbit radar to detect meteoroid streams present. This technique, which is much used particularly in photographic meteor work, is found to be inappropriate for use on radar data sets: while clusters corresponding to the major meteoroid streams are found in the AMOR data set, the algorithm is found to be very unstable and the statistical significance or otherwise of these clusters, and that of others whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…All observed radiants are located in the region of the Pisces constellation a few degrees above the ecliptic (dashed grey line). In addition, the positions of several meteor showers are marked: φ Aquariids [PAQ, #147 from Nilsson (1964)] and nine η Aquariids determined by different techniques and authors –Kashcheyev & Lebedinets (1967), Cook (1973), Sekanina (1973), Lindblad et al (1994), Galligan & Baggaley (2002), Galligan (2003), Brown et al (2008, 2009), Jopek et al (2008c). Also, we plotted the point representing theoretical radiant of the 1P/1909 Halley comet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All observed radiants are located in the region of the Pisces constellation a few degrees above the ecliptic (dashed grey line). In addition, the positions of several meteor showers are marked: φ Aquariids [PAQ, #147 from Nilsson (1964)] and nine η Aquariids determined by different techniques and authors –Kashcheyev & Lebedinets (1967), Cook (1973), Sekanina (1973), Lindblad et al (1994), Galligan & Baggaley (2002), Galligan (2003), Brown et al (2008, 2009), Jopek et al (2008c). Also, we plotted the point representing theoretical radiant of the 1P/1909 Halley comet.…”
Section: Discussionmentioning
confidence: 99%
“…Till now, the Southern hemisphere meteoroid streams were identified using orbits determined by a radar technique (Nilsson 1964; Gartrell & Elford 1975; Jopek, Valsecchi & Froeschlé 1999b; Galligan & Baggaley 2002; Galligan 2003). The aim of this paper was to search for streams among the meteors observed at the southern part of the Earth globe (first time) by a video technique.…”
Section: Introductionmentioning
confidence: 99%
“…They all tend to retrieve about 70% of simulated stream members in a noisy dataset of well-chosen cut-off levels (Galligan, 2003a(Galligan, , 2003b. Drummond (1981a) used a different set of weights to render each of the terms in natural units and linear over a similar range:…”
Section: (4)mentioning
confidence: 99%
“…The single linkage algorithm was used in asteroid studies (Zappala et al 1995) and in many meteoroid stream searches (Baggaley & Galligan 1997; Galligan 2003a,b). Zappala et al (1995) identified the dynamical families from a sample of 12 487 asteroids.…”
Section: Introductionmentioning
confidence: 99%